TANDA VISUAL PADA PERANGKO SATU ABAD MUHAMMADIYAH - Restu Ismoyo Aji (DeKaVe, 2011)
Muhammadiyah, one of the largest Islamic religious organization in Indonesia has been moving in to cultural, spiritual, and intellectual aspects since its beginning. Muhammadiyah's achievement appreciated not only by the Indonesian government but also by the Dutch Indies government. One of them through Centennial stamps of Muhammadiyah. From the selection of visual signs that are present on each stamp can be traced to the hidden meanings as well as the reason behind every specific objects in the stamp. Similarly, for the Centennary of Muhammadiyah Stamp. What, how, and why objects like the Masjid Gedhe Kauman Yogyakarta, KH Ahmad Dahlan, and The building University of Muhammadiyah Malang could be shown in all series of stamp.Keywords: stamp, Muhammadiyah, history.